Changing the Model for "Examining" Achievements in Writing A Case for International Collaboration? - Dixon, John.; Stratta, Leslie ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
A model for assessing student writing achievement uses sets of criteria to chart students' writing progress that are based on a study of exemplary samples of student writing produced at various stages of development. The model provides a viable alternative to assessment methods that call for students to produce lengthy essays on preselected topics in a limited time. Criteria for evaluating narratives based on personal experience are in the form of four questions: (1) What kinds of ordering occur as the writer imaginatively recounts past events? (2) How much audience awareness does the writer demonstrate? (3) How comprehensive is the writer's point of view? and (4) What actual or potential understanding of the uses of language does the writer demonstrate? Applying these criteria to a narrative example demonstrates their usefulness. Possible criteria for evaluating achievement in writing moral or social argument include questions on the complexity, coherence, and integrity of the argument, as well as the degree of the writer's awareness of opposing viewpoints. This analysis is in the spirit of investigations of writing development going on internationally and can contribute to a joint effort among English teachers to replace the old essay exam model. (AEA)
ERIC Note: Paper presented at the Annual Meeting of the International Conference on the Teaching of English (3rd, Sydney, Australia, August 17-22, 1980). Best copy available.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Content Analysis; Evaluation Criteria; Evaluation Methods; Models; Narration; Persuasive Discourse; Student Development; Student Evaluation; Writing (Composition); Writing Evaluation; Writing Processes; Writing Research; Reports, Evaluative